A complete MC optical photons tracking simulation of Plastic Scintillator Detectors for the next generation of satellite experiments. Issue 1 (1st November 2022) - Altomare, C.; Alemanno, F.; Barbato, F.C.T.; Bernardini, P.; Cattaneo, P.W.; De Mitri, I.; de Palma, F.; Di Venere, L.; Di Santo, M.; Fusco, P.; Gargano, F.; Kyratzis, D.; et al.
Abstract : Plastic scintillators are widely used for anti-coincidence systems and for the identification of charged cosmic-ray nuclei in satellite experiments. For this reason, a plastic scintillator detector (PSD) should have a high detection efficiency for charged cosmic rays and a very good capability of measuring charges. We implemented a full and customizable simulation tool to investigate the performance of a PSD coupled to Silicon Photomultipliers. The overall performance of the detector is studied by tracking optical photons produced inside the scintillator. The simulation will be used for the design of a PSD for future space experiments, such as HERD, AMEGO, e-Astrogam. In this work we investigated in detail the effect of Birks' saturation in the discrimination of charged ions up to iron nuclei. We will show the comparison between simulations and measurements conducted on prototype scintillator tiles.